Pengembangan Self-Esteem (Harga Diri) dalam Pembelajaran Pendidikan Agama Islam Di SMKN 1 Ponorogo - Ririn Nuraini (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2021)
This study aims: to determine the background of developing self-esteem in Islamic Religious Education (PAI) learning at SMKN 1 Ponorogo; to determine efforts to develop self-esteem in Islamic Religious Education (PAI) learning at SMKN 1 Ponorogo; as well as to determine the supporting and inhibiting factors of developing self-esteem at SMKN 1 Ponorogo. This research design is qualitative. Based on the process of data collection and analysis, this research resulted in: the background for developing self-esteem in Islamic Religious Education (PAI) learning at SMKN 1 Ponorogo is because PAI teachers see that students' self-esteem is still low; efforts to develop self-esteem (self-esteem) are very effective in terms of increasing self-esteem of students. These include: games or group games, motivational video screenings, and inspirational stories; as well as supporting and inhibiting factors for developing self-esteem in Islamic Religious Education Learning (PAI) at SMKN 1 Ponorogo including: student heterogeneity, backgrounds and problems that arise in the family, readiness of students and teachers.